Program Bimbingan Belajar Terhadap Anak-Anak di Desa Kalangsurya - Vidya Arisandi; Ajat Sudrajat (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The issue discussed in this service is to promote community service in literacy learning for children in the community in Kalangsurya village, Karawang district, West Java, Indonesia. The focus in this service is literacy in the form of tutoring for children in the Kalangsurya village environment, Karawang. The limitations discussed in this community service are the literacy of children in the village of Kalangsurya, Karawang in learning. The approach in this service is implementive and 'problem solving'. The purpose of this Community Service activity is to increase children's ability to learn so that children can be assisted and at the same time experience an increase in understanding the content of learning that they are not yet capable of. The benefit of this service is to help children learn subjects that children do in understanding subjects that children have not been able to solve in working on issues or subject topics that children have not been able to solve when studying. The result of this service is that the children are very enthusiastic and experience an increase in learning. The conclusions in this service show that this service with tutoring is very helpful for children in understanding the content of lessons in the village of Kalangsurya, Karawang.